COP27 Climate Change Conference: Urgent action needed for Africa and the world - Lukoye Atwoli; Gregory E. Erhabor; Aiah A. Gbakima; Abraham Haileamlak; Jean-Marie Kayembe Ntumba; James Kigera; Laurie Laybourn-Langton; Robert Mash; Joy Muhia; Fhumulani M. Mulaudzi; David Ofori-Adjei; Friday Okonofua; et al. (AOSIS, 2022)
No abstract available.